The swan princess [videorecording (DVD)] - Rich, Richard; Brown, Jared F.; Nissen, Brian; Palance, Jack, 1919-2006; Cleese, John; Wright, Steven, 1955-; Duncan, Sandy, 1946-; De Azevedo, Lex, 1943-; Zippel, David (Sony Pictures Home Entertainment, 2009)
The beautiful Princess Odette is transformed into a swan by an evil sorcerer's spell (which can only be broken by a vow of everlasting love) and held captive at an enchanted lake. There, she befriends Jean-Bob the frog, Speed the turtle and Puffn the bird. Despite their struggle to keep the princess safe, these good-natured animals can do nothing about the sorcerer's spell.